Reference-grade Taxus genome unleashes its pharmacological potential - Kui, L.; Majeed, A.; Dong, Y.
The genus Taxus is well known for its anticancer metabolite, paclitaxel. Recent releases of chromosome-scale reference genomes for two Taxus species (Xiong et al. and Cheng et al.)now provide novel insights on genome structure and phylogenomics and the origin and evolution of the paclitaxel biosynthesis pathway.
Keywords: TAXUS GENOME PACLITAXEL; WGD; TAXADIENE SYNTHASE